Skin moisture assessment using Hydration Sensor Patches coupled with smartphones via Near Field Communication (NFC). A pilot study with the first generation of patches that allow self‐recordings of skin hydration. Issue 5 (17th May 2021) - Flament, Frederic; Galliano, Anthony; Abric, Aurelie; Matoschitz, Christoph‐Manuel; Bammer, Manfred; Kampus, Miha; Kanda‐Diwidi, Diego; Chibout, Salim; Cassier, Matthieu; Delaunay, Caroline
Abstract: Objectives: To evaluate the potency of a new skin hydration sensor patch in the fast self‐recording of skin hydration. Material and methods: The Skin Hydration Sensor Patch (SHSP) turns the user's smartphone into a wireless skin moisture measuring device. The SHSP combines a capacitive measurement unit and Near Field Communication technology (NFC) for transmitting data and energy. The probe is fixed onto the back of the smartphone and pressed to the skin for a few seconds where the application immediately calculates the capacitance value. Once recorded, the probe is then immediately taken off from the skin. In a first study, this system was compared to the Corneometer ® technique, in vivo, on various skin sites of 23 healthy French women. In a second study, 20 women with moderate dry skin on face and forearm self‐recorded, through the SHSP the changes in skin hydration induced by a Xanthan gel containing 3% (w/w) of Glycerol, along 24 hours. A questionnaire based on 5 types of questions was established to be filled by subjects about their perception of the use of this new system. Results: In the first study, the values recorded by the SHSP were found highly correlated with those provided by the Corneometer ® . The second study allowed to observe significant differences in skin hydration of both sites at all times, as compared to values obtained before the application of the gel. Differences between both sites were observed, the face being less hydrated than forearm. From a practical aspect, the self‐recordings on the face show a higher variability (approx. 10% than those of the forearm). The questionnaire led to positive answers on almost all points. Conclusion: This SHSP appears as a promising approach in the field of connected skin‐related devices. As such, it opens or enlarges a new paradigm in the relationships between a consumer and a cosmetic product.